Excess Competition among Food Hubs - Cleary, Rebecca; Goetz, Stephan J.; McFadden, Dawn Thilmany; Ge, Houtian (Journal of agricultural and resource economics, 2019)
Food hubs offer a novel solution to connect small and mid-sized local farms, which individually lack the scale to profitably market their products. Because many food hubs rely on grants and philanthropy to provide services and are not necessarily profit-driven, markets may unintentionally oversaturate due to overinvestment. We use a firm-entry model to estimate the average U.S. county population necessary for one, two, and three food hubs to break even. Our findings suggest that policy makers and philanthropists need to consider the carrying capacity of the local food environment and population prior to supporting additional food hubs.